Novel indole based hybrid oxadiazole scaffolds with N-(substituted-phenyl)butanamides: synthesis, lineweaver–burk plot evaluation and binding analysis of potent urease inhibitors. Issue 46 (19th July 2018) - Nazir, Majid; Abbasi, Muhammad Athar; Aziz-ur-Rehman,; Siddiqui, Sabahat Zahra; Raza, Hussain; Hassan, Mubashir; Ali Shah, Syed Adnan; Shahid, Muhammad; Seo, Sung-Yum
Abstract : In the study presented herein, 4-(1 H -indol-3-yl)butanoic acid (1 ) was sequentially transformed in the first phase into ethyl 4-(1 H -indol-3-yl)butanoate (2 ), 4-(1 H -indol-3-yl)butanohydrazide (3 ) and 5-[3-(1 H -indol-3-yl)propyl]-1, 3, 4-oxadiazole-2-thiol (4 ) as a nucleophile. Abstract : In the study presented herein, 4-(1 H -indol-3-yl)butanoic acid (1 ) was sequentially transformed in the first phase into ethyl 4-(1 H -indol-3-yl)butanoate (2 ), 4-(1 H -indol-3-yl)butanohydrazide (3 ) and 5-[3-(1 H -indol-3-yl)propyl]-1, 3, 4-oxadiazole-2-thiol (4 ) as a nucleophile. In the second phase, various electrophiles were synthesized by reacting substituted-anilines, 5a–j, with 4-chlorobutanoyl chloride (6 ) to afford 4-chloro- N -(substituted-phenyl)butanamides (7a–j ). In the final phase, nucleophilic substitution reaction of4 was carried out with different electrophiles, 7a–j, to achieve novel indole based oxadiazole scaffolds with N -(substituted-phenyl)butamides (8a–j ). The structural confirmation of all the as-synthesized compounds was performed by spectral and elemental analysis. These molecules were screened for their in vitro inhibitory potential against urease enzyme and were found to be potent inhibitors. The results of enzyme inhibitory kinetics showed that compound8c inhibited the enzyme competitively with a K i value 0.003 μM. The results of the in silico study of these scaffolds were in full agreement with the experimental data and the ligands showed good binding energy values. The hemolytic study revealed their mild cytotoxicity towards cell membranes and hence, these molecules can be regarded as valuable therapeutic agents in drug designing programs.